Kampanye Pengasuhan Positif Melalui Buku Kecil (Booklet) Kepada Orangtua Dari Anak Prasekolah di Surabaya - Agnes Maria Sumargi; Eli Prasetyo; Made Dharmawan Rama Adhyatma (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Many parents have difficulties in managing their child behavior. Therefore, positive parenting campaign through dissemination of parenting booklets was designed to help parents to understand and implement positive parenting strategies. Booklets were developed in two versions. The printed version of booklets were distributed to parents in two preschools/kindergartens in Surabaya, and the electronic version of booklets were disseminated via WhatsApp messenger. Sixty-nine parents responded to the evaluation survey. The majority reported that their parenting knowledge increased and they intended to implement positive parenting tips in the booklets. Some parents would like to spend more time with their children, pay more attention to their child behavior, and improve their teamwork with the other child caregivers. Overall, parents received benefits from reading the booklets and supported further development of the booklets